What Will Happen to the US Textile and Apparel Industry if the NAFTA Goes?. (May 2018) - Lu, Sheng
This study provides a quantitative evaluation of how the termination of the North American Free Trade Agreement (NAFTA) proposed by the Trump administration will affect the US textile and apparel (T&A) industry. By adopting the Global Trade Analysis Project (GTAP) computable general equilibrium model based on the GTAP9 database, the study finds that: first, the termination of NAFTA will significantly reduce US apparel imports from NAFTA members but lead to an increase of US apparel imports from Asian countries; second, ending NAFTA will substantially reduce US textile exports to the NAFTA region, which currently is the single largest export market for the US textile industry; and third, rather than encouraging more 'Made in the USA', the termination of NAFTA will reduce further the output of T&A manufacturing in the United States. The findings of this study augment our understanding of the potential economic impact of ending a major free trade agreement, which has been studied little, and shed new lights on the debate regarding the T&A-specific sectoral impact of NAFTA. The findings of the study also provide valuable inputs for policymakers regarding what should or should not be done with NAFTA from the perspective of the US T&A industry. JEL Classification: F14, F15, F17